Public policies and education regulation: issues under debate - Kadzerski, Chaiane Oliveira (Universidade Estadual de Campinas, 2016)
The book published by Editora Mercado de letras - Campinas, SP is a collection of works by researchers from Brazil and other countries, namely Mexico and Portugal. Its main focus is the policy options and regulatory practices in the industry, reflecting and sharing the analysis of the issues and dilemmas that cross contemporary educational policies. The work of Dr. Elton Luiz Nardi (Unoesc), Maria de Lourdes Pinto de Almeida (Unoesc / Unicamp), and Isabel Maria Torres Carvalho Viana (UM), has nine chapters organized in two parts, the first one reserved for the "Trends, agendas and imperatives of the regulation of education" and the second part, for the debates of "policies and regulation of education in Brazil".